Clinical Outcomes of Ezetimibe Plus Statins in Patients With Lower Extremity Artery Disease - Yoshihiro Iwasaki, MD, PhD; Takenobu Shimada, MD, PhD; Takefumi Kishimori, MD; Atsuyuki Wada, MD, PhD; Jumpei Koike, MD; Takehiro Matsumoto, MD, PhD; Takafumi Yagi, MD; Masaharu Okada, MD, PhD (JACC: Advances)
Background: The beneficial outcomes of ezetimibe plus statin therapy are well-established in coronary artery disease, but these remain unknown in lower extremity artery disease (LEAD). Objectives: This study evaluated the efficacy of an intensified lipid-lowering strategy involving ezetimibe plus statins vs statin monotherapy for reducing major adverse limb events and mortality in patients with LEAD. Methods: This retrospective analysis included patients aged ≥18 years diagnosed with LEAD from the TriNetX global health care database from 2013 to 2022, excluding those with recent acute coronary syndrome or stroke. The primary outcome was the 12-month cumulative incidence of major lower limb amputation and all-cause death as a composite endpoint. Propensity score matching was used to adjust for baseline characteristics and confounders, yielding 4,204 patients in each group. Results: The composite endpoint was lower with statins plus ezetimibe vs statin monotherapy (5.8% vs 10.2%; P < 0.001; HR: 0.54; 95% CI: 0.46-0.64). Taken individually, both major lower limb amputation (2.7% vs 4.6%; P < 0.001; HR: 0.57; 95% CI: 0.45-0.72) and all-cause death (3.4% vs 6.3%; P < 0.001; HR: 0.52; 95% CI: 0.42-0.65) were significantly lower with combination therapy. Subgroup analyses showed consistent effects across all subgroups. Conclusions: Compared to statin monotherapy, an intensified lipid-lowering strategy (ie, ezetimibe plus statins), significantly reduced the incidence of major lower limb amputation and all-cause mortality in real-world patients with LEAD.